PAH: beyond the idiopathic form of disease - T. A. Martynyuk (IP Morozov P.V., 2020)
VIII Eurasian Congress of Cardiology. Overview of symposiums. PAH: beyond the idiopathic form of disease. Systemic Hypertension.